Managing delinquency the case of Pag-ibig Fund Housing Loan borrowers - Garcesto, Aireen Gail Marie V.
All men are born with basic needs and desires. Apart from our basic wants such as food and clothing, we also need shelter. A loan is a type of debt. Like all debt instruments, a loan entails the redistribution of financial assets over time, between the lender and the borrower. Acting as a provider of loan is one of the principal task for financial institutions like PAG-IBIG Fund. The borrower incurs a type of debt called mortgage which is a very common type of debt instrument used by many individuals to purchase housing. The borrower initially receives an amount of money from the lender which they pay back, usually but not always in regular installments to the lender. This service is generally provided at a cost, referred to as interest on the debt. Delinquency is a failure of a borrower to make timely mortgage payments under a loan agreement. This study discussed matter pertaining housing loan delinquency and what PAG-IBIG Fund can do for delinquent borrowers. This also determined the significant influence of socio-demographic characteristics to delinquent housing loan borrowers. This study covered socio-demographic characteristics of housing loan borrowers especially the delinquent ones, the reason for delinquency and remediation measures.. socio-demographic characteristics include age, sex, employment status, highest educational attainment, monthly income and housing loan information. The study was conducted at PAG-IBIG Fund. Data were gathered using interview schedule. Respondents were randomly selected from the list of delinquent borrowers. Descriptive statistics especially frequency and percentage were used to analyze data and information gathered by the study. Delinquencies are unavoidable. Changes in employment and income, marital status, and personal crises are among the factors that contribute to loans being delinquent or default. These factors cannot be anticipated regardless of the housing process and criteria. Delinquencies are the result of housing expenses that were not anticipated by the household or debt taken on after receiving the loan. Finally, delinquents may result for the servicing and collecting practices of the fund. The fund has a list of remediation measures for those who are interested. These are reminders, done through telephones or counseling. There lso issuance of demand letters, notification of foreclosure and introduction to the Housing Loan Restructuring Program.